(untitled) (LEARNing Landscapes, 2020)
This autoethnographic essay describes an ambulatory workshop with fellow graduate students, a walking tour to remote parts of campus where we paused to consider writing prompts and to create short performative sketches highlighting the nature of our relationships to the land around us. In this reflection on our “walk and talk,” I consider how teachers and students co-create what we learn together, the mysteries of engaging in interactive drama and poetry methods, and the performative ways in which we might come to know the places where we live and work more intimately and more imaginatively.